Autism Spectrum Disorder Detection from Parents Dialogues Using Multinomial Naïve Bayes and XGBoost Models - Mukherjee, Prasenjit; Sadhukhan, Sourav; Godse, Manish (International Journal of Computer Sciences and Engineering, 2024)
To indicate the proper development of a child, there are certain baseline milestones. If a child is not reaching the milestones at the expected rate, it can indicate that there is an issue that needs to be addressed. By early intervention, the development of the child can be improved and the long-term impact of the developmental delays may be reduced. One such constraint of child development is Autism spectrum disorder. The ASD-affected children exhibit difficulties in communication, socialization and challenges in physical, social, and emotional development. This neurodevelopmental disorganization may exhibit an extensive range of effects and symptoms including challenges in communication, social interactions, and physical, social, and emotional behaviours. To identify ASD symptoms in a child, the range of ASD symptoms must be available as datasets to the researchers. The difficult phenomenon is that parents are not able to identify or detect early-age indications of ASD in their children. This proposed research work aims to detect the symptoms of ASD from parents’ dialogues. The dataset has collected data from many autism groups from social media and organizations for special children. To understand the sentiment of parents’ dialog there are two important and popular machine learning models, the Multinomial Naïve Bayes and the XGBoost. Naïve Bayes is based on a probabilistic machine learning model and XGBoost is an ensemble-oriented model. If new data comes from a new parent, the sentiment of that data is also predicted by these models. By using these two models, sentiment analysis can help to identify ASD symptoms. Based on the prepared data, the accuracy of these two models is 70% and 70% respectively.